Unilateral tax reform under the restricted origin principle - Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
We analyze the restricted origin principle for taxing international trade in a three-country, three-commodity model where two of the countries form an economic union. Using simplifying assumptions with respect to the initial tax equilibrium and the structure of preferences, the effects of a Variation in one union country's general com-modity tax rate on relative prices and national welfare in each of the trading nations are derived. It is argued that each of the union countries can increase the domestic tax base at the expense of its union partner by reducing the general commodity tax rate. This suggests that a process of downward tax competition between union members might take place under the restricted origin principle.
Keywords: 330